2000
DOI: 10.1002/1529-0131(200004)43:4<821::aid-anr12>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Expression of osteoclast differentiation factor at sites of bone erosion in collagen-induced arthritis

Abstract: Focal bone erosion in CIA is attributed to cells expressing definitive features of osteoclasts, including CTR. The expression of RANKL by cells within inflamed synovium suggests a mechanism for osteoclast differentiation and activation at sites of bone erosion. Inhibitors of RANKL may represent a novel approach to treatment of bone loss in rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
117
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(120 citation statements)
references
References 21 publications
(32 reference statements)
1
117
0
1
Order By: Relevance
“…Macrophages possess broad proinflammatory, destructive, and remodeling capacities and contribute considerably to inflammation and joint destruction in both the acute and chronic phases of RA (23). Osteoclasts, which can derive from monocytes (2,3), are known to contribute to focal bone erosion in RA and in animal models of arthritis (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages possess broad proinflammatory, destructive, and remodeling capacities and contribute considerably to inflammation and joint destruction in both the acute and chronic phases of RA (23). Osteoclasts, which can derive from monocytes (2,3), are known to contribute to focal bone erosion in RA and in animal models of arthritis (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Bone loss is a common feature of various inflammatory arthritides (1). Osteoclasts, which can be generated from peripheral monocytes (2,3), are known to contribute to focal bone erosion in rheumatoid arthritis (RA) (4)(5)(6) and in animal models of arthritis (7,8).…”
mentioning
confidence: 99%
“…While the mechanisms of cartilage destruction in RA have been evaluated in detail, much less is known about destruction of articular bone. With regard to bone, there is evidence for an important role of osteoclasts in RA (1)(2)(3). In healthy individuals, bone remodeling is conducted by osteoblasts synthesizing bone matrix and its resorption by osteoclasts.…”
mentioning
confidence: 99%
“…Moreover, the presence of RANKL in organs such as lymph nodes, spleen, thymus, and intestinal lymphoid patches has been described (9,10,18). RANKL is increased upon exposure to factors that promote osteoclast development, such as vitamin D 3 and prostaglandin E 2 (PGE 2 ), which also diminish the expression of OPG by osteoblasts (19). RANKL also plays an important role in differentiation of osteoclasts from their precursor cells and promotes increased activity and survival of these cells by inducing antiapoptotic effects, leading to bone resorption (8,15).…”
mentioning
confidence: 99%
“…Although the etiology of RA is not yet fully understood, recent studies have suggested an involvement of autoantibody production, immune complex formation, inflammatory cell infiltration and tumor-like proliferation of synovium ''pannus'' in the pathogenesis of RA [6,16,20]. In addition, activation of osteoclasts in RA is associated with skeletal tissue destruction [2,7,18,19]. RA treatment is currently mainly based on the administration of nonsteroidal anti-inflammatory drugs (NSAID), corticosteroid preparation, disease-modifying anti-rheumatic drugs and molecularly targeted drugs such as indomethacin, prednisolone, methotrexate and infliximab [26].…”
Section: Introductionmentioning
confidence: 99%